An Efforts to Prevent Juvenile Delinquency to Prepare the Nation's Successful Generation - Widayati Widayati; Winanto Winanto; Arpangi Arpangi; Apitta Fitria Rahmawati (LAW FACULTY UNISSULA, 2022)
This research aims to analysis the problems of teenagers who the next generation who will continue and realize the ideals of the nation. We are about to enter the Golden Indonesia in 2045, which will certainly be the era of today's youth. However, the rapid development of information technology has caused the problems and challenges faced by teenagers to become more severe and complex. The method used in the implementation of this community service activity is through lectures, showing pictures and videos, asking questions, and discussing. Those who cannot use it properly will fall into juvenile delinquency with behavior that deviates from societal norms, religious norms and ethics. The causes of juvenile delinquency are various, including lack of parental attention, lack of religious education, wrong associations, and mistakes in utilizing advances in information technology. The solution offered is to provide an understanding to the public about the causes of juvenile delinquency and its impact, the use of useful information technology, how to prevent juvenile delinquency, and directing the youth to carry out positive and beneficial activities for themselves, their families, and the environment.